Comparison of Toxic Metal Concentrations in Antidiabetic Herbal Preparations (ADHPs) Available in Bangladesh Using AAS and XRF Analytical Tools - Zamir, Rausan (ScientificWorldJournal, 2019)
Widespread escalation of type 2 diabetes is a concern throughout the world. Developing countries are leading with patients suffering from diabetes-related complications. Plant-based therapeutic, antidiabetic herbal preparations (ADHPs) are being sought for long and the consumption is increasing in in Bangladesh. Plant-based antidiabetic preparations do not go through the screening procedure in terms of safety. Toxic metals in ADHPs have been investigated by two different methods: atomic absorption spectroscopy (AAS) and X-ray fluorescence (XRF). Then, metal concentrations obtained by AAS and XRF were compared. A total of eleven ADHPs were subjected to nondestructive XRF analysis and destructive AAS analysis. Results from the two methods were analyzed statistically by Pearson correlation coefficient (PCC), r(xy). Pearson correlation coefficients were found to be −0.05, 0.94, and 1.00 for Mn, Cu, and Zn, respectively. Zn and Cu had significant strong positive correlation (r(xy) = 1.00 and 0.94, respectively); however, very weak negative correlation was observed in Mn (r(xy) = −0.05). The concentrations were regressed to observe the presence of linearity. Linear correlation was found for Zn and Cu which indicates a good agreement between AAS and XRF. However, very weak linear correlation in Mn indicates necessitating requirements for further investigation on getting scientific evidence of toxic metal assessment of the antidiabetic herbal preparations for searching and establishing instrumental agreement.